Landbank Electronic Modified Disbursement System: Status, Challenges, And Opportunities for Enhancement (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study examined the adoption, performance, challenges, and enhancement opportunities of the LANDBANK Electronic Modified Disbursement System (eMDS) at the Boac Branch in Marinduque, Philippines. Using a mixed-method design, survey data were collected from 26 eMDS users (clients and employees) and complemented by qualitative feedback. Results indicate a very high level of system adoption and satisfaction (composite mean = 3.87, Strongly Agree), with users rating eMDS as efficient, secure, and preferable to manual disbursement processes. Key challenges identified include transaction delays during peak usage (WM = 2.69) and system lag under limited internet connectivity (WM = 2.73), despite generally strong perceptions of system stability. Users also reported high confidence in security features (composite mean = 3.85) and workflow efficiency (composite mean = 3.69). The findings underscore the importance of optimizing transaction speed, improving low-bandwidth performance, and strengthening embedded user support tools. Anchored on the Sustainable Development Goals, the study highlights how eMDS contributes to SDGs 8, 9, 10, and 16 by enhancing efficiency, inclusivity, and transparency in public financial management.